Developing a chair based exercise programme for older people in a community setting - Robinson, Katharine (2017)
Background Exercise has well known health benefits for older people, however, for some older people with compromised health and mobility participating in exercise is challenging. Chair based exercise is a pragmatic and accessible form of exercise that may be offered in this context, however, there is a lack of good quality evidence and a lack of standardisation in delivery. Method This thesis used the Medical Research Council’s framework for the development and evaluation of complex interventions to develop a community delivered chair based exercise intervention – Progressive Assisted Chair Exercise (PACE). Multiple research methods were undertaken to develop a theoretically driven intervention with a clear rationale for how it was anticipated to work. This included an expert consensus development process, a systematic review of randomised controlled trial literature, and identification of literature on the physiological and behaviour change principles of exercise for older people. The PACE intervention was then tested in a pre and post cohort study in an NHS community service to establish the feasibility of the intervention and whether it resulted in the anticipated outcomes. The acceptability of the intervention was explored through focus groups with older people. Results Experts agreed on a set of 46 principles of chair based exercise through a Delphi technique. The systematic review of randomised controlled trials identified a lack of consistent and good quality evidence for the health benefits of existing programmes. Greater focus on the development of programmes that were underpinned by a sound theoretical framework was recommended. Using the findings from the expert consensus, the systematic review and published guidelines on exercise for older people the PACE intervention was developed to include a 12 week multi-component progressive group or home based programme delivered by a healthcare professional with the knowledge and skills of working with older people and targeted at older people who were unable to participate in standing exercise programmes. The pre and post cohort study demonstrated that the programme was feasible to deliver when tailored to account for individual preferences and the fluctuating health needs of older people. The programme was acceptable to older people when targeted appropriately at those unable to participate in standing programmes and when individual preferences and needs were accounted for. The primary criteria for success of clinically meaningful improvements in lower limb muscle strength and progression to supported standing exercise were observed. Conclusions The PACE intervention as a complex intervention was sufficiently developed and modelled to warrant formal evaluation. Further feasibility work is needed to optimise the evaluation method through a feasibility randomised controlled trial. Further development work for care home and acute rehabilitation populations is indicated.